Citizen Scientists as Human Subjects: Ethical Issues - David B. Resnik (Citizen Science: Theory and Practice, 2019)
An increasing number of human studies are asking participants to have substantial involvement in research. Citizens in human studies may contribute to various research activities, including study design, recruitment, data interpretation, and data and sample collection. Citizen involvement in research raises novel ethical issues for human studies, because individuals have traditionally occupied the role of researcher or subject, but not both at the same time. The confluence of these two different roles in the same person poses challenges for investigators and oversight committees because legal rules and ethical guidelines focus on protecting the rights and welfare of human subjects and do not address issues that fall outside this domain, such as study design, data quality and integrity, reporting misconduct, authorship, or publication. This article examines some of these issues and makes recommendations for investigators and oversight committees.